2019
DOI: 10.1590/s1984-29612019086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of tick-borne pathogens in small mammals from Brazilian Amazonia

Abstract: Small non-volant mammals (marsupials and small rodents) were captured at three different timepoints from 23 forest fragments across three municipalities (Alta Floresta, Sinop and Cláudia) covering the Amazonian biome of the Mato Grosso State in Midwestern Brazil. The animal tissues (liver and spleen) and blood were screened using molecular tools for the detection of Babesia, Coxiella, Cytauxzoon, Hepatozoon, Theileria, and Anaplasmataceae agents. A total of 230 specimens (78 rodents and 152 marsupials) were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
11
1
5
Order By: Relevance
“…Regarding the other PCR assays of the present study, none of the samples yielded detectable DNA to Piroplasmorida agents. This result contrasts with previous studies that reported different Piroplasmorida haplotypes among small mammals from other regions of Brazil, including studies that employed the same PCR protocol of the present study [ 3 , 20 , 24 , 39 ]. Therefore, these contrasting results could be related to uneven distribution of Piroplasmorida agents among the populations of small mammals along different geographical regions of Brazil, due to reasons yet to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the other PCR assays of the present study, none of the samples yielded detectable DNA to Piroplasmorida agents. This result contrasts with previous studies that reported different Piroplasmorida haplotypes among small mammals from other regions of Brazil, including studies that employed the same PCR protocol of the present study [ 3 , 20 , 24 , 39 ]. Therefore, these contrasting results could be related to uneven distribution of Piroplasmorida agents among the populations of small mammals along different geographical regions of Brazil, due to reasons yet to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, a novel piroplasmid closely related to a Babesia sp. detected in Monodelphis domestica opossums from the Brazilian Pantanal has been found in D. marsupialis opossums from the Brazilian Amazon (Soares et al, 2017), and another Piroplasmida genotype was reported in two/31 (6.45%) D. marsupialis trapped in Sinop municipality, State of Mato Grosso (Colle et al, 2019). In the present study, all white-eared opossums tested negative for Theileria/Babesia spp.…”
supporting
confidence: 65%
“…Estudos em busca de patógenos transmitidos por carrapatos já foram realizados em animais de vida livre, bem como em seus ectoparasitas no Brasil (MERINO et al, 2008;WIDMER et al, 2011;ALMEIDA et al, 2013;WOLF et al, 2016;SOARES et al, 2017a,b;MONGRUEL et al, 2017, COLLE et al, 2019, PERLES et al, 2019, MUNÕZ-LEAL et al, 2019DE OLIVEIRA et al, 2020;MUÑOZ-LEAL et al, 2021a), porém o foco em pequenos mamíferos tem sido muito menor.…”
Section: Doenças Transmitidas Por Vetores Provaram Ser Inquestionávei...unclassified
“…Por outro lado, existem muitos estudos relatando a ocorrência de espécies de Hepatozoon em carnívoros, marsupiais, roedores, répteis e anfíbios, (ANDRE et al, 2010;PERLES et al, 2019;SANTOS et al, 2020;MAIA et al, 2014;DEMONER et al, 2016). Estudos recentes em roedores e marsupiais encontraram haplótipos que nas suas análises filogenéticas aparecem em um grande clado composto por haplótipos associados a roedores, marsupiais e répteis, inferindo assim que essas espécies provavelmente estejam sim relacionadas como hospedeiros paratênicos, e se infectem através da predação (WOLF et al, 2016;COLLE et al, 2019;DEMONER et al, 2019;SILVA et al, 2017;DEMONER et al, 2016).…”
Section: Doenças Transmitidas Por Vetores Provaram Ser Inquestionávei...unclassified
See 1 more Smart Citation